Phylogenetic systematics of Tertiary monophorasterid sand dollars (Clypeasteroida: Echinoidea) from South America - Mooi, Rich (2000)
Sand dollars in the Monophorasteridae Lahille, 1896, form an important part of the South American Cenozoic echinoid fauna. Re-examination of type and other material adds significantly to our knowledge of the morphology and taxonomy of the family, and shows that besides Monophoraster darwini (Desor, 1847), M. duboisi (Cotteau, 1884), Amplaster coloniensis Martinez, 1984, and A. alatus Rossi de Garcia and Levy, 1989, there is a new species, A. ellipticus. We also show that Karlaster Marchesini Santos, 1958, is not a monophorasterid as once thought. A phylogenetic analysis of 24 characters assessed from all species of Monophoraster Lambert and Thiery, 1921, and Amplaster Martinez, 1984, along with genera of the Mellitidae Stefanini, 1912, produced a single most parsimonious tree. The analysis demonstrates monophyly of mellitids and monophorasterids, and that Iheringiella Berg, 1898, should be excluded from the latter. Although both Monophoraster Lambert and Thiery, 1921, and Amplaster Martinez, 1984, retain many features of an ancestor in common with the Mellitidae Stefanini, 1912, they also exhibit bizarre morphologies quite different from those of mellitids. The study has also resulted in a clearer picture of the biogeography and biostratigraphy of the Monophorasteridae, and their great significance in the evolution of lunulate sand dollars in the Americas.